Inheritance of the ebony Trait in Drosophila Melanogaster through Reciprocal Crosses - Najmadina Aulia Hanifa; Talita Dwi Ardiningrum; Alya Galuh Kirana; Ajwah Ulya Sahira; Muslih Munadi Amin; Muhamad Justitia Ramadhan (Rifa'Institute, 2026)
Introduction: Mendel’s First Law states that allele pairs segregate during gamete formation, producing predictable inheritance patterns. The ebony body-color mutation in Drosophila melanogaster is a useful model for studying Mendelian inheritance. Objective: This study aimed to verify the segregation pattern of the ebony trait and determine whether its inheritance is autosomal or sex-linked. Method: A Completely Randomized Design with two reciprocal crossing treatments, female normal × male ebony and female ebony × male normal, was conducted from February to April 2026. Second-generation offspring were classified into normal and ebony phenotypes and analyzed using the Chi-square test. Result and Discussion: The female normal × male ebony cross produced 354 normal and 116 ebony individuals, yielding a ratio of 3.05:1. The reciprocal cross produced 578 normal and 195 ebony individuals with a ratio of 2.96:1. All Chi-square values were lower than 3.84, indicating agreement with the expected 3:1 ratio. Similar results from both reciprocal crosses indicate that inheritance of the trait is independent of parental sex. Conclusion: The ebony trait in Drosophila melanogaster is inherited as an autosomal recessive allele in accordance with Mendel’s First Law of Segregation